Correlation of The Implementation Therapeutic Communication with Patient Satisfaction in The Inpatient Room - Noor Amaliah; Dyah Ustriani; Yustan Azidin (MBUnivPress, 2023)
The hospital is a health service institution for the community. Nurses as officers who are always in contact with patients must have many skills, one of which is communication with patients. Therapeutic communication is communication that is specifically structured, has a purpose and focuses on the client. Communication is one of the factors in determining patient satisfaction. This study aims to determine the relationship between the implementation of therapeutic communication with patient satisfaction in the Inpatient Room. This research was a correlation research with a cross sectional approach. The population in this study were all beds in the inpatient unit, namely 48 beds, meaning 48 patients. The sample used was 47 patients with simple random sampling technique. The research instrument used was respondent characteristics, therapeutic communication questionnaire, and patient satisfaction. Data analysis used fisher's exact test. Therapeutic communication of nurses in the inpatient room was good as many as 30 people (63,8%). Patient satisfaction in the inpatient room with a satisfied category of 39 people (83%). There is a correlation between the implementation of nurse therapeutic communication with patient satisfaction in the inpatient room (p value 0,019).